Laparoscopic findings in chronic pelvic pain - Bajracharya, J; Shrestha, NS; Karki, C; Saha, R (Journal of Kathmandu Medical College, 2013)
Background: Chronic pelvic pain is a common problem in reproductive age group women. Diagnosis of chronic pelvic pain needs multidisciplinary approach. Diagnostic laparoscopy is one of the investigations which can help in reaching the diagnosis. Objective: To know the etiology in chronic pelvic pain. Methods: This was a descriptive study done in the Department of Obstetrics and Gynaecology of Kathmandu medical college teaching hospital from January 2010 to June 2012 (30 months). All the cases of laparoscopic surgery done for chronic pelvic pain were noted and details of these cases were analyzed regarding age, parity and laparoscopic findings. Results: Total 48 cases of Chronic Pelvic Pain underwent diagnostic laparoscopy during the study period. Mean age of cases were 33 years, ranging from 20-46yrs. Almost half of the cases 43.75% were of parity two. Laparoscopic finding was negative in 29.17% and pelvic pathology was present in 70.83% of the cases. Out of the pelvic pathology endometriosis was present in 55.88% followed by pelvic adhesions, pelvic congestion and pelvic inflammatory disease, chronic ectopic in 20.58%, 14.70%, 5.88%, 2.94% respectively. Conclusion: Diagnostic laparoscopy is a useful modality in the diagnosis of etiology and management of Chronic pelvic pain. In our study, Pelvic endometriosis was the most common pelvic pathology in cases of Chronic pelvic pain. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8146 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 100-102